Teaching for quality learning: a leadership challenge - Konting, Mohd Majid (Universiti Putra Malaysia Press, 2016)
Many educational policies, strategies and action plans are developed based on the available theories and best practices. As learning is central to educational success, this lecture reexamines the field of education, particularly learning and teaching, and how research findings have informed policy development and practices in effecting teaching for quality learning – meaningful change in the knowledge, skills, attitude and behaviour of the learner. First, it explores the dynamic field of education, learning and teaching, zooming into the changing focus of teaching towards student-centred, self-determined, deep and meaningful learning in the wake of 21st century education. Second, teacher effectiveness will be scrutinised to understand how the notion, amid differences in its conception, could bring about impactful teaching on learning. Third, using four major studies undertaken over a span of three decades, teacher and lecturer beliefs and their classroom practices will be analysed to investigate their struggle in implementing the recommended student-centred pedagogies, culminating in the barometer of policy success in educational reforms, and arguing the case of improving teaching for quality learning. The first study highlights how ‘effective’ teachers grapple to understand the concept of student-centredness and teacher effectiveness, implying that continuous empirical investigations are necessary to embed their beliefs and practices that are characteristics of effective teaching for quality learning and, hence, to illuminate the progress of curriculum development and implementation in the uniquely Malaysian context. The second study, the recipient of the Washington Symphony’s International High Notes in Education Award for the year 2000 and has been emulated in the Korean Smart Education initiative, indicates the level of teachers’ and students’ knowledge about smart teaching and learning, confirming the widely held belief that issues of information dilution are widespread in the top-down innovation process, thereby suggesting that a more engaging teacher training strategy should be employed in implementing successful innovation. The third study emphasises the necessity for high order thinking skills as well as a more effective model of teacher recruiting, training, and career development that have become the thrusts of the Malaysia Education Blueprint 2013-2025 (Preschool to Post-Secondary Education). The final study encapsulates the findings of 15 student-centredness inquiries in higher education institutions that express the demand for a more effective training programme on pedagogy and the need to develop leadership in the pursuit of teaching for quality learning. Fourth, based on the research findings, teacher and academic training and development will be reexamined to facilitate teachers and lecturers. Finally, this lecture explores educational leadership, a contentious but promising academic field of research that has tremendous potential to facilitate the transformation agenda of teaching and learning being put forward in volumes of policies, strategies and action plans. Indeed, visionary, persistent, engaging, continuous and well-informed efforts to bring substantial and sustainable changes in teaching for quality learning, especially through teacher and lecture development and leadership, are pertinent for educational reform.